The Dynamic Role of Religious Figures in The Diffusion of Community Forest Development: A Study of Phenomenology on Madurese Community in Probolinggo Regecny - Tirmidi, Tirmidi; Kanto, Sanggar; Hidayat, Kliwon; Luth, Thohir (Universitas Nurul Jadid, 2021)
One of the causes of the successful development of community forests in Probolinggo Regency was the participation of religious leaders. This study explored the dynamics of the role of religious leaders in the development of community forests. Through a qualitative research design with a phenomenological approach and a Naturalistic paradigm, it was found that religious leaders carried out dynamic roles from the pioneering period to the period of obtaining international ecolabel certificates. From this discovery, three propositions were drawn to which after inter-relation between the concepts, two substantive theories were drawn, namely (1) Followers’ Need-Based Visionary Leader Theory, dan (2) Theory of Change-and-Innovation Enabling Leader Quality (Attributes of Change-and-innovation Enabling Leader).